SPIRITUALITAS DAN LANDASAN SPIRITUAL (MODERN AND ISLAMIC VALUES); DEFINISI DAN RELASINYA DENGAN KEPEMIMPINAN PENDIDIKAN - Faizah, Kurniyatul (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2021)
Spirituality is not something foreign to humans, because it is the core (core) of humanity itself. Manpu's spiritual drive brings the material dimension of man to his spiritual dimension (spirit, divinity) by understanding and internalizing His attributes, living life according to His instructions and imitating His Messenger. The goal is to gain His pleasure, to become a "friend" of Allah, "lover" (wali) of Allah. Spiritual leadership is leadership capable of inspiring, arousing, influencing and mobilizing through exemplary, service, compassion and the implementation of values ​​and other divine traits in goals, processes, culture and leadership behavior. The spiritual leadership model is not only influenced by external factors, but is more guided by internal factors, namely the human conscience, but spiritual leadership does not mean anti-intellectual leadership. The leadership implemented by Muhammad SAW. become a role model with its main characteristics, namely siddiq (integrity), trust (trust), fathanah (working smart) and tabligh (openly, human relations) capable of influencing others by inspiring without indoctrinating, awakening without hurting, arousing without forcing and inviting without ordering. Spiritual leadership in schools or madrasas really needs to be applied by the principal, because madrasas are schools or places to study both general science and Islamic religious knowledge, and what characterizes madrasas are very focused on cultivating values. or the science of religion for students where the aim of the madrasa in general is to form a human who understands religion (to be a human being who is faithful and pious). So ideally, a principal, especially at a school with an Islamic background or known as a madrasa, should be able to apply spiritual leadership in carrying out its main duties and functions.